Difficulty Analysis of Solving HOTS Problems on Harmonic Vibration Using Heller Troubleshooting - Elsiaulavita Gracia; Haratua Tiur Maria; M. Musa Syarif Hidayatullah (Jurnal Pendidikan Fisika, 2022)
This research was conducted with the aim of knowing the types and causes of difficulties experienced by students in solving HOTS questions on harmonic vibration material. This research is a qualitative descriptive study. The study was conducted at SMA Negeri 10 Pontianak with a total sample of 44 people. Data collection techniques are giving HOTS test questions and interviews to students of class XI science. Data analysis is done by reducing data, presenting data, and making conclusions. experiences experienced by students in accordance with Heller's problem solving. Based on the results of the study, it is known that the factors causing students to be less than optimal in solving HOTS questions (1) difficulty visualizing problems caused by students not understanding the questions, and lack of habituation to rotate the questions. the problem in the question becomes an image; (2) lack of ability to understand the problem; (3) lack of understanding of the concept; (4) errors in the physical description stage and the solution plan stage, students do not know the concepts used in the problem, and do not master arithmetic operations; (5) students are in a hurry and are less thorough in completing and checking answers. The average percentage of difficulties experienced by students is 85.17% with a very high category.